EFEKTIVITAS MODEL PEMBELAJARAN ROLE PLAYING DALAM MENINGKATKAN PEMAHAMAN SISWA TERHADAP MATERI KISAH HIJRAH PADA MATA PELAJARAN PAI DI SMPN 7 BANDUNG - Yustian, Yunus; Asyafah, Abas; Firmansyah, Mokhammad Iman (TARBAWY : Indonesian Journal of Islamic Education, 2017)
This present study is primarily based on the low of activities and learning results of the students in class VIII SMP Negeri 7 Bandung on Islamic Education subject, particularly in story materials, which are caused by the implementation of inappropriate learning model. The design used in this carried out study was quasi experimental design using non-equivalent control group design. Then, the instruments used in this study were in the form of objective tests of cognitive domain using multiple choices question. In the process of data analysis, this study performed normality test, homogeneity test, normalized gain calculation, and t-test consisting of paired sample test and independent sample test. The results showed that there was a significant difference, in which the experimental class was considered to be better than the control class (2-tailed sig. value was 0.000). For further study, it is suggested that the collaborative learning model of role playing type can be applied in the field of Islamic Education subject aside from the story materials by considering the advantages and disadvantages of this model.Penelitian ini dilatarbelakangi rendahnya aktivitas dan hasil belajar siswa kelas VIII SMP Negeri 7 Bandung pada mata pelajaran PAI materi kisah, yang disebabkan kurang tepatnya model pembelajaran. Desain penelitian yang digunakan adalah kuasi eksperimen dengan bentuk nonequivalent control grup design. Instrumen yang digunakan berupa tes objektifÂ  ranah kognitif dengan bentuk soal pilihan ganda. Analisis data meliputi uji normalitas, uji homogenitas, perhitungan gain ternormalisasi, uji t-test yang terdiri dari uji paired sample test dan uji independent sample test. Hasil penelitian menunjukkan terdapat perbedaan signifikan, dimana kelas eksperimen lebih baik daripada kelas kontrol (nilai sig. 2-tailed sebesar 0,000). Bagi peneliti selanjutnya agar model pembelajaran kolaboratif tipe role playing dapat diterapkan pada ruang lingkup PAI di luar materi kisah dengan memperhatikan kelebihan dan kekurangan model ini.Â Kata Kunci: Efektivitas, Model Kolaboratif Tipe Role Playing, Pemahaman Siswa.